Use of lithium in clozapine-induced neutropenia: a case report - Suraweera, Chathurie; Hanwella, Raveen; De Silva, Varuni (Springer Nature, 2014)
Background: The literature describing the long-term use of lithium carbonate to reinstate reduced levels of white blood cell counts in patients treated with clozapine is scarce. We describe a case of successful recommencement of clozapine on a patient who developed risk level of neutropenia which was corrected by lithium carbonate. He was followed up for a period of one year. Case presentation: We report a 40-year-old Sri Lankan male who developed neutropenia and low white blood cell counts following commencement of clozapine. We were successful in restarting clozapine after the addition of lithium carbonate to increase the cell counts. Clozapine was increased to 700 mg a day with 500 mg of lithium carbonate. The patient remains stable after one year with no further episodes of neutropenia. Conclusion: Lithium carbonate can successfully be used to treat clozapine-induced neutropenia.
Keywords: Lithium carbonate; Neutropenia; Clozapine